Braving the SARS-CoV-2 Pandemic – Quandary of Health-Care Workers - Singh, Arjun Gurmeet; Chaturvedi, Pankaj (Indian Journal of Medical and Paediatric Oncology, 2020)
Determining how bad health-care providers have been affected by the severe acute respiratory syndrome coronavirus 19 (SARS-CoV-19) pandemic is difficult because governments and organizations have not released this data.The aim of the study was to determine the number of health-care workers infected and dead globally due to SARS-CoV-2 infection.To circumvent these issues, an unconventional approach using Google's programming platform was adopted to aggregate relevant articles reporting the number of confirmed cases and deaths among health-care workers. Locally sourced country-specific data were ensured by individually searching the regional domains of 179 countries.Reports covering 67 countries showed that 99,847 health-care workers (HCWs) have been reported to be infected with SARS-CoV-2 virus, with a majority reported in Europe. This included confirmed reports of 1732 doctors and 348 nurses. Five hundred and thirty-eight deaths were reported in 32 countries, amounting to a mortality among HCWs globally of 4%.Although this number might be an underrepresentation of the actual figures out there, it underscores the dire reality of the situation. The information provided is paramount for policymakers to improve services among this vulnerable group.
Keywords: Coronavirus disease 2019; doctors; health-care workers; nurses; severe acute respiratory syndrome coronavirus 2